Fatigue Crack Detection Using Nonlinear Acoustic-Analysis Of Vibro-Acoustic Modulation - Jenal, Ruztamreen; Abdullah, Mohd Azman; J. Staszewski, Wieslaw (2012)
Nonlinear vibro-acoustic is a highly reliable and sensitive method for damage detection. It is a method based on propagation of high frequency acoustic waves in solid structures with low-frequency excitation. Interaction of the acoustic wave with material or geometry properties changes caused wave distortion effects. The causes called nonlinear acoustic effects are amplified with the low frequency excitation. Nonlinear acoustic-acoustic modulations are investigated for fatigue crack detection. The focus is on vibro-acoustic wave moduIations used for crack detection in aluminium. Experimental works are performed to investigate the effect of crack characteristics, i.e. crack lengths and crack modes, on vibro-acoustic effects intensity. Nonlinear acoustic tests are performed for the uncracked and cracked aluminium plates. The analyses results show that there are many nonlinear phenomena (i-e. hysteresis and classical Ist order perturbation) involved in the vibro-acoustic wave modulations. The nonlinear modulations produced by the low-frequency modal excitation and high-frequency ultrasonic excitation can be used effectively for fatigue crack detection.